THE INFLUENCE OF THE TUNNEL CONSTRUCTION PROCESS ON THE DEFORMATION OF THE SOIL AROUND THE TUNNEL AND PRECIPITATION OF THE EARTH’S SURFACE - Normurodov Shakhboz Ulugbekovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents issues related to the creation of reliable circular cross-sections of tunnels, taking into account the voltages around the artificial spaces located in the grunt massif, and the high speed of tunnel excavation work, as well as the operation of tunnel excavation mechanisms, safe for workers-employees and surface structures, the high-quality processing of the tunnel coating.